Effects of Drying Time on Yield and Moisture Content of “Sumahe” Powdered Drink Using Spray Dryer - Ismiyati Ismiyati; Fatma Sari; Ratri Ariatmi Nugrahani; Anwar Ilmar Ramadhan (Graduate Program of Syiah Kuala University, 2018)
As people today are becoming more health-conscious, various efforts have been made to keep up one’s health, such as by consuming highly nutritious food and drinks. One of the nutritious food sources produced from bees is honey, bioactive compounds of polyphenols, glyoxal and methylglioxal. Honey could be used as a health drink by mixing with ginger. This health drink is also produced as powdered drink to simplify storing, reduce the use of plastic packaging, and to add product value to increase market share. The aim of this research was to analyze the effects of drying time for 5, 15, and 25 minutes with an addition of maltodextrin on the yield, density, and moisture content of “Sumahe” instant powdered drink, made from cow’s milk, honey, and ginger. The results showed that the longer the drying time, the lower the moisture content of the drink. Meanwhile, the longer the drying time, the higher the yield became. A taste test of “Sumahe” also indicated that from 25 minutes of drying time, most of the panelists rated the drink as tasteful and delicious.